PERAN KIYAI DALAM MENGEMBANGKAN PONDOK PESANTREN DI ABAD 21 - Yasin Nahrowi; Asif maulana; Fitria Rahayu; fiqra muhammad nazib (Advances In Education Journal, 2025)
The role of the kiyai in developing Islamic boarding schools (pondok pesantren) in the 21st century is crucial, especially in facing the challenges of globalization in the fields of technology, economy, and culture. In this digital era, pesantren, as traditional educational institutions, are confronted with the need to integrate technology into the learning process without compromising the Islamic values that form the foundation of their education. As leaders and administrators, kiyai play a strategic role in guiding pesantren to adapt to the development of information and communication technologies, thus enhancing the quality of education and presenting pesantren as relevant institutions in the modern world. In the economic sphere, kiyai contribute to the economic independence of pesantren by managing businesses based on Islamic principles and empowering santri (students) to become entrepreneurs. Meanwhile, in the cultural domain, kiyai play a role in preserving and developing local cultures while promoting pesantren as a center of Islamic culture that helps preserve traditional cultural values amidst the forces of modernization. Therefore, the role of kiyai in developing pesantren is essential in addressing the challenges of the times and maintaining the existence of pesantren in the 21st century.